BODIPY appended copper(ii) complexes of curcumin showing mitochondria targeted remarkable photocytotoxicity in visible light1. Issue 5 (13th May 2015) - Bhattacharyya, Arnab; Dixit, Akanksha; Mitra, Koushambi; Banerjee, Samya; Karande, Anjali A.; Chakravarty, Akhil R.
<x xml:space="preserve">Abstract</x> BODIPY-appended copper(ii) complexes of curcumin show a remarkable PDT effect in visible light in HeLa cells via apoptosis with mitochondrial localization.